2007
DOI: 10.1080/00420980601023836
|View full text |Cite
|
Sign up to set email alerts
|

The Dysfunctions of Markets, Hierarchies and Networks in the Meta-governance of Partnership

Abstract: Governments increasingly see partnerships as their delivery instrument of choice. There is disagreement, however, about how the proliferation of these institutions should be understood. One interpretation sees ungovernability, instability and unaccountability in the fragmented institutions of local governance. Another maintains that the new approaches to co-ordination have allowed for the reassertion of hierarchical control. On the basis of a theoretical exposition of the logic of co-ordination and a study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 59 publications
2
32
2
Order By: Relevance
“…The most effective networks in our sample had such a balanced combination; while in seven out of 16 cases of the less effective networks such a balance was absence. The literature [27] has focused on tensions among governance mechanisms, but from a control perspective, especially in a complex health care environment, a balanced combination of governance mechanisms might increase rather than reduce network effectiveness [33]. Hence, our study does not confirm the findings of Entwistle et al [27], who point at hierarchy and contracts as sources of dysfunctions in networks.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The most effective networks in our sample had such a balanced combination; while in seven out of 16 cases of the less effective networks such a balance was absence. The literature [27] has focused on tensions among governance mechanisms, but from a control perspective, especially in a complex health care environment, a balanced combination of governance mechanisms might increase rather than reduce network effectiveness [33]. Hence, our study does not confirm the findings of Entwistle et al [27], who point at hierarchy and contracts as sources of dysfunctions in networks.…”
Section: Discussioncontrasting
confidence: 77%
“…The latter is typically associated with networks [14,15]. Relational governance refers to co-ordination based on trust, reciprocity, and common norms and values that are embedded in the relationships between the partners in networks [14,15,27-29]. Markets are governed by contracts and pricing mechanisms [30].…”
Section: Methodsmentioning
confidence: 99%
“…As noted in the literature review, collaboration is often merely a façade (Almog-Bar and Zychlinski 2012). While Brinkerhoff (2002) proposed that partnership be used as an ideal type against which all other relationships are measured (Brinkerhoff 2002), sometimes, as Entwistle et al (2007) found, NPOs were critical of their 'partnerships' with government. True collaboration was distorted due to the power differentials driven by hierarchical and market logics underpinning the contractual relationship.…”
Section: Cooperationmentioning
confidence: 97%
“…Besides the failures of coordination mechanisms and the possible mix of market, networks and hierarchies (Entwistle et al 2007), there is also discussion on the ambiguous nature of decision-making in governance networks. Rhodes (1997) claims that urban regeneration in the UK is characterised by an interdependent network of state and non-state actors that is undermining the power of the state.…”
Section: Governance Network: Ambiguity and Critiquementioning
confidence: 99%
“…This is sometimes described as mixed-economy coordination (Bradach and Eccles 1989). These authors argue that each coordination mechanism has its advantages and disadvantages and the viability of a coordination mechanism depends on the characteristics of the actors involved, the issues at stake and context of decision-making (Entwistle et al 2007). …”
Section: Network Governance In Urban Renewalmentioning
confidence: 99%